Metal-Free ipso-Selenocyanation of Arylboronic Acids Using Malononitrile and Selenium Dioxide - Redon, Sébastien; Kosso, Anne Roly Obah; Broggi, Julie; Vanelle, Patrice (Synthesis, 2019)
The first ipso-selenocyanation of arylboronic acids is achieved using selenium dioxide and malononitrile under mild conditions. The reaction is successful even without metal or base in DMSO. The major advantages of this new method are an easy set-up, excellent yields, and the use of odorless and inexpensive selenium reagents. Basic conditions subsequently afford new access to diaryldiselenides in good yields without isolating the organoselenocyanate intermediates.
Keywords: selenocyanate; arylboronic acid; selenium dioxide; malononitrile; diaryldiselenide